(90)Y SPECT/CT quantitative study and comparison of uptake with pretreatment (99 m)Tc‐MAA SPECT/CT in radiomicrosphere therapy - Debebe, Senait Aknaw (J Appl Clin Med Phys, 2019)
INTRODUCTION: Yttrium‐90 ((90)Y) microsphere post‐treatment imaging reflects the true distribution characteristics of microspheres in the tumor and liver compartments. However, due to its decay spectra profile lacking a pronounced photopeak, the bremsstrahlung imaging for (90)Y has inherent limitations. The absorbed dose calculations for (90)Y microspheres radiomicrosphere therapy (RMT) sustain a limitation due to the poor quality of (90)Y imaging. The aim of this study was to develop quantitative methods to improve the post‐treatment (90)Y bremsstrahlung single photon emission tomography (SPECT)/computed tomography (CT) image analysis for dosimetric purposes and to perform a quantitative comparison with the (99m)Tc‐MAA SPECT/CT images, which is used for theranostics purposes for liver and tumor dosimetry. METHODS: Pre and post‐treatment SPECT/CT data of patients who underwent RMT for primary or metastatic liver cancer were acquired. A Jasczak phantom with eight spherical inserts of various sizes was used to obtain optimal iteration number for the contrast recovery algorithm for improving (90)Y bremsstrahlung SPECT/CT images. Comparison of uptake on (99m)Tc‐MAA and (90)Y microsphere SPECT/CT images was assessed using tumor to healthy liver ratios (TLRs). The voxel dosimetry technique was used to estimate absorbed doses. Absorbed doses within the tumor and healthy part of the liver were also investigated for correlation with administered activity. RESULTS: Improvement in CNR and contrast recovery coefficients on patient and phantom (90)Y bremsstrahlung SPECT/CT images respectively were achieved. The (99m)Tc‐MAA and (90)Y microspheres SPECT/CT images showed significant uptake correlation (r = 0.9, P = 0.05) with mean TLR of 9.4 ± 9.2 and 5.0 ± 2.2, respectively. The correlation between the administered activity and tumor absorbed dose was weak (r = 0.5, P > 0.05), however, healthy liver absorbed dose increased with administered activity (r = 0.8, P = 0.0). CONCLUSIONS: This study demonstrated correlation in mean TLR between (99m)Tc‐MAA and (90)Y microsphere SPECT/CT.